Hubungan Antara Faktor Sosial Ekonomi dan Migrasi di Kecamatan Palaran - Bang Ekes; Michael MS; Agus Junaidi (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
The purpose of this study was to determine the relationship between Age, Income, Education and Migration in the Palaran’s District. The theory used in this research is the migration theory and the theory of economic development. The research using qualitative data in the form of primary data obtained from interviews, conducted by investigators to obtain information sample respondents to fill out questionnaires. The methods of analysis used in this study were Univariate and Bivariate using two-dimensional Contingency Tables and program SPSS (Statistical Program For Science) version 20. The Data analysis can be concluded that : (1) There are dependency relationship but not significant between the variables of age with migration at  (2) There are a significant dependency relationship between the variables of income with migration variable (3) There are a significant dependency relationship but not significant between elementary school, junior high school with migration, but high school, university and migration variables there are a significant dependency (4) There are association relationship but not significant between the variables of age with migration (5) There are a significant association relationship between the variables of income with migrations variables   (6) There are association relationship but not significant between elementary school, junior high school with migration but high school, university with migrations variables there are a significant association.Keywords:  Age, Income, Socioeconomic and Migration.